Entre o comércio informal e as margens do ilegal: práticas de trabalho na Rua 25 de Março - Aguiar, Ana Lidia de Oliveira [UNIFESP] (2013)
The 25th March Street in Sao Paulo City can be comprehended from the relation of several formal and informal jobs, unregulated and illegal markets present in a daily basis. At this street goods and actors circulate and compose an extensive and complex trading network. This requires taking different ways to organize and to deal with the many situations which met in this urban space. The multiple form of jobs presented in the street accessing the field of informal economy dictates, often through illegal practices for the acquisition and sale of goods. In this scenario of informalities and frequent illegalities, workers face a conflict situation in their performance, acting through tactics and cleverness against numerous social and institutional actors, especially in areas were the State is concerned. By this means, workers socialize with their peers, creating strategies to work in advance the intense scrutiny. These actors develop processes of identity and production, highlighting a perception of differences by workers of the street that are configured on the intersections and tensions between them, in relation to formal and illegal markets, and finally the State. As a result, I looked for understanding how these processes were dealt with by agents and scales of government towards new urban projects that are often played through repression and surveillance.